The yin and yang of leukotriene B4 mediated inflammation in cancer. (October 2017) - Jala, Venkatakrishna R.; Bodduluri, Sobha R.; Satpathy, Shuchismita R.; Chheda, Zinal; Sharma, Rajesh K.; Haribabu, Bodduluri
Abstract: The high affinity leukotriene B4 receptor, BLT1 mediates chemotaxis of diverse leukocyte subsets to the sites of infection or inflammation. Whereas the pathological functions of LTB4 /BLT1 axis in allergy, autoimmunity and cardiovascular disorders are well established; its role in cancer is only beginning to emerge. In this review, we summarize recent findings on LTB4 /BLT1 axis enabling distinct outcomes toward tumor progression. In a mouse lung tumor model promoted by silicosis-induced inflammation, genetic deletion of BLT1 attenuated neutrophilic inflammation and tumor promotion. In contrast, in a spontaneous model of intestinal tumorigenesis, absence of BLT1 led to defective mucosal host response, altered microbiota and bacteria dependent colon tumor progression. Furthermore, BLT1 mediated CD8 + T cell recruitment was shown to be essential for initiating anti-tumor immunity in number of xenograft models and is critical for effective PD1 based immunotherapy. BLT2 mediated chemotherapy resistance, tumor promotion and metastasis are also discussed. This new information points to a paradigm shift in our understanding of the LTB4 pathways in cancer.